BIOLOGICAL EVALUATION AND QSAR STUDIES OF SOME SYNTHETIC PYRAZOLONE COMPOUNDS - KISHOR ARORA,; VEENA NATHANI, (International Journal of Pharma and Bio Sciences, 2015)
Some novel synthetic pyrazolone compounds were evaluated for their biological activity. Structures of these compounds have been established on the basis of their melting point and Infrared spectral data. All the compounds were screened for their antifungal activity by disc diffusion methodof measuring the zone of inhibition and found that the compounds viz. 4- Amino antipyrine thiosemicarbazone (C-8) and 1-(4-Sulfoamidophenyl)-3-methyl-5-pyrazolone (C-10) showed significant antifungal activity against Sclerotium rolfsii.Quantitative Structure Activity Relationship (QSAR) investigation with a stepwise linear regression analysis was applied to find a correlation between different calculated physico-chemical parameters of the compounds and biological activity.